The Effects of Sorbed Alkali Metal Ions on the Conductance of Activated Carbon - Badri, M.; Crouse, Karen Anne; Awang , Harun (1985)
The rate of increase of the conductance of activated carbon immersed in NaCl solutions was found to be lOE.'er when the concentration of the salt was increased. This was probably due to the increase in the viscosity of the solutions which prevented the filling of the pores to the same extent as in the case of pure water. In addition, the final conductance of the sample was also lowered. The opposite effect was however observed in HCl solution. Measurements in the presence of Li + and K + suggested that the mobility of the ions determined the.final value.